THEORETICAL RESEARCH OF SOCIAL ENTREPRENEURSHIP IN THE REGION (ON THE EXAMPLE OF THE ATYRAU REGION) - M.K. Baymuhasheva; R.K. Sabirovа (Academic Journal of Physical and Chemical Sciences, 2019)
Social entrepreneurship in modern society involves an altruistic business style that focuses on social benefits. This influence is considered by the social entrepreneur as a profit, since the success of a social enterprise depends on a number of factors related to social influence and not priority for traditional enterprises. Therefore, some authors believe that the difference between “entrepreneurship” and “social entrepreneurship” lies primarily in goal-setting: unlike classical entrepreneurs, social entrepreneurs do not seek to extract maximum profits, but aim at changing unfair social conditions, creating products or social change services.